Bioaccumulation of the Heavy Metal Mercury (Hg) and Proximate Content of Gracilaria sp. on Lombok Island - Ghazali, Mursal; Adhawati, Laela; Pazila, Baiq Dinda Aluh Putri; Artiningrum, Novitaa Tri; Candri, Dining Aidil; Rizki, Anis Syakiratur; Lestari, Dinda Propita; Hasanto, Rizki Primaditya; Nurhayati, Nurhayati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
One of the dangerous heavy metals that can build up in aquatic biota is mercury (Hg). The purpose of this study was to evaluate the environmental health condition in possibly polluted areas near Pelangan Village, Sekotong Subdistrict, West Lombok, and to ascertain the heavy metal level in Gracilaria sp. Using samples taken from Pelangan, Elak-Elak, and Mentigi, the Atomic Absorption Spectrophotometer (AAS) method was used to analyze non-essential heavy metal pollution in Gracilaria sp. According to the findings, Gracilaria samples taken from the Sekotong Subdistrict's coastline area had the greatest levels of mercury pollution, with 0.05 mg/kg in Elak-Elak and 0.14 mg/kg in Pelangan. On the other hand, samples of Gracilaria sp. from the Mentigi coast in North Lombok did not exhibit any mercury contamination (0.00 mg/kg). The levels of mercury accumulation in Gracilaria sp. are classified as dangerous since they surpass the 0.03 mg/kg maximum permissible limit for mercury in consumable products established by the Indonesian National Standard (SNI 7387:2009). Additionally, Gracilaria substrate samples from Pelangan had a mercury contamination level of 0.05 mg/kg, greater than that of Mentigi and Elak-Elak (both at 0.00 mg/kg). The proximate content of Graciaria sp was influenced by the sampling location but was not influenced by mercury contamination.